FAKTOR-FAKTOR YANG MENGHAMBAT COMING OUT PADA LESBI FEMME DI BALI - Dewi, I Gst Ayu Puspasari; Tobing, David Hizkia (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
In psychology, lesbian has not regarded as a psychiatric disorder since 1973 until now based on guidebook of the DSM (Diagnostic and Statistical Manual of Mental Disorder). But until now presence of lesbians on the society are still faced with a denial and violation of religion, norms, and values prevailing in society. In Indonesia, especially in Bali, lesbian being as individual mostly